Effect of quenching on post-processed aluminum 6082 alloy using friction stir processing. (2022) - Yadav, Sukhvir; Sharma, Sanjeev; Singh, Bhupender; Sharma, P.B.
Abstract: Recently, experimentation on cooling media alteration during Friction Stir Processing (FSP) had put impetus efforts to analyzing the effects on microstructures of Aluminum alloys. On the other hand, developing alternative cooling processes like the artificial aging of post-processed FSPed components is also seized the consideration to study the grain refinement of Al-Alloys. This work focuses on studying the effects of oil quenching on FSPed Al 6082 alloy after completing the conventional procedure. Unconventional to the air cooling and water cooling during the machining process, the post-processed Al 6082 alloy (PPA) was submerged for two hours in an oil bath, and effects on microstructure, microhardness, and tensile strength were compared with conventional cooling media. The increments that occurred in microhardness and tensile strength revealed that the PPA had gained mechanical strength after oil quenching. Subsequently, PPA's microstructure became coarser unlike the conventional characteristic of the FSPed specimen.